2017
DOI: 10.1056/nejmoa1606490
|View full text |Cite
|
Sign up to set email alerts
|

Anti–Interleukin-31 Receptor A Antibody for Atopic Dermatitis

Abstract: In this phase 2 trial, nemolizumab at all monthly doses significantly improved pruritus in patients with moderate-to-severe atopic dermatitis, which showed the efficacy of targeting interleukin-31 receptor A. The limited size and length of the trial preclude conclusions regarding adverse events. (Funded by Chugai Pharmaceutical; XCIMA ClinicalTrials.gov number, NCT01986933 .).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
397
0
16

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 500 publications
(423 citation statements)
references
References 39 publications
10
397
0
16
Order By: Relevance
“…Side effects were nearly negligible encompassing increased creatine phosphokinase levels in the treatment group compared to placebo. A phase II study of nemolizumab in 264 AD patients (moderate to severe) unable to adequately control disease activity by topical therapy shows significantly decreased pruritus [58]. However, despite marked reductions of both the EASI and SCORAD severity scores, these changes did not reach levels of statistical significance possibly due to sample size.…”
Section: Nemolizumabmentioning
confidence: 99%
“…Side effects were nearly negligible encompassing increased creatine phosphokinase levels in the treatment group compared to placebo. A phase II study of nemolizumab in 264 AD patients (moderate to severe) unable to adequately control disease activity by topical therapy shows significantly decreased pruritus [58]. However, despite marked reductions of both the EASI and SCORAD severity scores, these changes did not reach levels of statistical significance possibly due to sample size.…”
Section: Nemolizumabmentioning
confidence: 99%
“…Notably, therapy with ustekinumab that inhibits the common p40 subunit of IL-12/IL-23 and thus the production of IL-17, IL-21, and IL-22, was not effective in patients with moderate to very severe AD [153, 154]. A 12-week therapy with nemolizumab, the anti-IL-31 receptor antibody, was shown to dramatically reduce pruritus and in parallel improve clinical signs of AD in a phase 2 study underlining the role of the itch-scratch cycle [155]. …”
Section: Therapeutic Management Of Admentioning
confidence: 99%
“…In a recently published phase II trial, an anti-IL-31 receptor A antibody, nemolizumab, resulted in significantly improved pruritus in patients with moderate-to-severe atopic dermatitis. 10 In a companion article in this issue, Gangemi et al 11 reported on their systematic review, which provided a timely in-depth overview regarding the role of IL-31 in skin diseases.…”
mentioning
confidence: 99%